PERAN TEOLOGI KRISTEN DALAM PENDIDIKAN KRISTEN BERKARAKTER DALAM MEMBANGUN MODERASI BERAGAMA DI ERA KONTEMPORER - Damaris Kalua'; Yermia; Herlina Talo; Gustri Mahardika; Yunus Adi (Jurnal Salome : Multidisipliner Keilmuan, 2025)
Christian theology has a central role in shaping Christian education with character, especially in facing the challenges of the contemporary era. Christian education does not only aim to form intellectuals, but also develops morality and attitudes of religious moderation. In the context of pluralism, religious moderation is an important value to foster attitudes of tolerance, dialogue and respect for differences. Christian theology based on love, justice and peace can be the basis for building a Christian education curriculum that instills the values ​​of religious moderation. By applying this approach, Christian education can form students who have a strong faith and are able to live side by side with others in diversity. This article analyzes how Christian theology can strengthen Christian education in instilling the value of religious moderation as a response to social and cultural challenges in the modern era.